2020
DOI: 10.3390/medicina56060271
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Integrated Health Systems in Africa: A Systematic Review

Abstract: Background and objective: Traditional medicine (TM) was integrated into health systems in Africa due to its importance within the health delivery setup in fostering increased health care accessibility through safe practices. However, the quality of integrated health systems in Africa has not been assessed since its implementation. The objective of this paper was to extensively and systematically review the effectiveness of integrated health systems in Africa. Materials and Methods: A systematic literature sear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 37 publications
1
9
0
Order By: Relevance
“…Participants, irrespective of professional background and location of affiliated institutions, were aware of the presence of integrated health facilities and the TM Department at KNUST. This finding confirms the result of a Ghanaian study [ 25 ] and a systematic review that assessed the effectiveness of integrated health systems in Africa [ 27 ]. The framework for integrating TM into national health systems clearly specifies that the availability and acquisition of health information is crucial to the building of an effective integrated system [ 6 ].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Participants, irrespective of professional background and location of affiliated institutions, were aware of the presence of integrated health facilities and the TM Department at KNUST. This finding confirms the result of a Ghanaian study [ 25 ] and a systematic review that assessed the effectiveness of integrated health systems in Africa [ 27 ]. The framework for integrating TM into national health systems clearly specifies that the availability and acquisition of health information is crucial to the building of an effective integrated system [ 6 ].…”
Section: Discussionsupporting
confidence: 89%
“…TM was introduced into the orthodox health system through a series of health interventions to take advantage of the strengths of both systems. These interventions include the formulation of a TM policy in 2005, establishment of the TM council in 2010 to oversee the activities of TM practitioners, inauguration of TM into the tertiary educational system, and establishment of the Centre for Scientific Research into Plant Medicine in 1975 [ 5 , 24 , 27 ]. Since 2012, TM units have been created in 17 health facilities across the country [ 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…In 2013, it was reported that approximately 70% of Ghanaians rely on TM for healthcare [21]. The integration of TM into the Ghanaian health system was triggered by the high prevalence of TM use among the populace [22]. In Ghana, TM is used to cure and manage ailments such as fevers, cuts, foot rots, stroke, cancer, and diabetes [10,21,23].…”
Section: Introductionmentioning
confidence: 99%
“…Difficulties in bridging the gap between indigenous and Western scientific paradigms have been widely discussed in the literature [ 110 , 111 ]. However, some examples of collaborative initiatives concerning the human health care system demonstrate that the dichotomy between Western veterinary medicine and African healing methods can be overcome, allowing for the development of hybrid knowledge that evolves and is continually redefined [ 111 , 112 ]. Ref.…”
Section: Resultsmentioning
confidence: 99%